Geometric Remodeling of the Perirenal Aortic Neck at and Adjacent to the Double Sealing Ring of the Anaconda Stent-Graft After Endovascular Aneurysm Repair. - Koenrades, Maaike A.; Bosscher, Marianne R. F.; Ubbink, Jouke T.; Slump, Cornelis H.; Geelkerken, Robert H. (Journal of Endovascular Therapy, 2019)
Purpose: To evaluate if the radial force of the double sealing ring of the Anaconda stent-graft induces dilatation in the perirenal aortic neck adjacent to the rings. Materials and Methods: This study evaluated the serial electrocardiogram-gated computed tomography scans of 15 abdominal aortic aneurysm patients (mean age 72.8±3.7 years; 14 men) who were treated electively using an Anaconda stent-graft. Follow-up scans were conducted before discharge and at 1, 6, 12, and 24 months after endovascular repair. Diameter and area were assessed perpendicular to the aortic centerline along the perirenal aortic neck, which was subdivided into 3 zones: the suprastent, the stent, and the infrastent zones. Measurements were performed independently by 2 experienced observers using dedicated 3-dimensional image processing software. Results: Between discharge and the 2-year follow-up the diameter and area remained stable in the suprastent zone [average diameter change: −0.1±0.4 mm (−0.4%±1.7%), p=0.893; average area change: −2.9±17.2 mm2 (−0.7%±3.4%), p=0.946], increased in the stent zone [average diameter change: +1.9±1.0 mm (+7.3%±4.0%), p<0.001; average area change: +84.3±48.3 mm2 (+15.5%±8.7%), p<0.001], and diverged in the infrastent zone [average diameter change: −0.8±2.2 mm (−2.3%±7.4%), p>0.99; average area change: −34.6±102.3 mm2 (−4.1%±14.8%), p>0.99; increased in 4 patients, decreased in 9 patients]. Conclusion: After Anaconda implantation the infrarenal aortic neck accommodated to the expansion of the sealing rings at the stent zone. Below the stent zone the neck diameter decreased in the majority of patients, while an increase was related to downstream displacement of the main body. A decrease in size in the infrastent zone may contribute to durable sealing and fixation. A personalized follow-up scheme based on geometric neck remodeling should be feasible if our observations are confirmed in larger, long-term studies.